Problems of Legal Regulation of Human Organ and Tissue Transplantation Relations - SHEVCHUK, Svetlana Stepanovna; IBRAGIMOVA, Nazima Shafievna; BELANOVA, Galina Olegovna; MALYKHINA, Mariya Alekseevna; IVAKHNENKO, Svetlana Nikolaevna (Journal of Advanced Research in Law and Economics, 2017)
This paper is devoted to research and analysis of the issues on legal regulation of the relations arising in connection with the removal of human organs or tissues with the purpose of their subsequent transplantation to a donor. The current national legal framework and lawenforcement practice in transplantation relations are investigated. The theoretical and practical problems affecting the provision and protection of the rights and interests of parties to these relations are analyzed. The necessity of further development and improvement of legal regulation of transplantation relations is substantiated. The scientific novelty of the work is that the authors, on the basis of studying the history of the formation and development of the institution of human organ and tissue transplantation, have made attempts to identify the main trends and directions of legislative support of this sphere of social relations and to substantiate the most constructive proposals in order to improve the corresponding mechanism of legal regulation.